Methodological essence of scientific and technical innovative products - Kobielieva, T. O.; Klymentova, M. V.; Pererva, P. G. (My University, 2023)
It is well-founded that the demand for scientific and technical products in the world is constantly growing, since it is directly related, on the one hand, to the improvement and development of existing industries in order to increase their technical level and economic efficiency, and on the other hand, to the renewal of products, with the release of new highly competitive products. And although the development and creation of scientific and technical products is carried out most often within the framework of contracts concluded between manufacturing enterprises (firms) and scientific organizations, as well as within the framework of a state order, nevertheless, a significant number of scientific and technical products enter the foreign market.
Методологічна сутність науково-технічної інноваційної продукції
Keywords: innovative activity; products; intellectual property; legislation; enterprises